Metabolism or behavior: explaining the performance of aphids on alkaloid-producing fungal endophytes in annual ryegrass (Lolium multiflorum) - Bastias Campos, Daniel (2017)
Plant–herbivore interactions are often mediated by plant microorganisms, and the “defensive mutualism” of epichloid fungal endophytes of grasses is an example. These endophytes synthesize bioactive alkaloids that generally have detrimental effects on the performance of insect herbivores, but the underlying mechanisms are not well understood. Our objective was to determine whether changes in the physiology and/or behavior of aphids explain the changes in performance of insects feeding on endophytic plants. We studied the interaction between the aphid Rhopalosiphum padi and the annual ryegrass Lolium multiflorum symbiotic (E+) or not symbiotic (E−) with the fungus Epichloë occultans that can synthesize loline alkaloids. We hypothesized that aphids feeding on E+ plants have higher energetic demands for detoxification of fungal alkaloids, thereby negatively impacting the individual performance, population growth, and structure. Aphids growing on E+ plants had lower values in morphometric and functional variables of individual performance, displayed lower birth rate, smaller population size, and dramatic structural changes. However, aphids exhibited lower values of standard metabolic rate (SMR) on E+ plants, which suggests no high costs of detoxification. Behavioral variables during the first 8 h of feeding showed that aphids did not change the phloem sap ingestion with the presence of fungal endophytes. We hypothesize that aphids may maintain phloem sap ingestion according to their fungal alkaloid tolerance capacity. In other words, when alkaloid concentrations overcome tolerance threshold, ingestion of phloem should decrease, which may explain the observed lower values of SMR in E+ feeding aphids.